Empowering the Community of Gang Dolly Surabaya by Improving English Skills in Daily Conversations - Suyanto, Suyanto; Standsyah, Rahmawati Erma; Tobing, Victor Maroli Tua Lumban (Society : Jurnal Pengabdian Masyarakat, 2024)
The purpose of this empowerment activity is to develop the quality of the Gang Dolly community to support the economy which has shrunk due to the closure of the localization area in the region. Empowerment activities are carried out with socialization and training in English, which expected to make Kampung Dolly become like an English village in Pare Village, Kediri. The empowerment activities took place in 2018 for about 6 months, with the result that 70% of the people who participated in this activity obtained a satisfactory rating. This result shows that people around the area are still wanted to learn and local government should give them the acces.